Risk factors for periprosthetic femoral fractures around total hip arthroplasty: a systematic review and meta‐analysis. Issue 4 (16th October 2019) - Deng, Yi; Kieser, David; Wyatt, Michael; Stringer, Mark; Frampton, Christopher; Hooper, Gary
Abstract: Background: Periprosthetic fractures are becoming increasingly common, often leading to poor patient outcomes. The aim of this study was to identify risk factors associated with periprosthetic femoral fractures (PPFFx). Methods: Two independent reviewers conducted a systematic review of the databases MEDLINE, Embase and Cochrane Library according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, from the earliest available date to December 2017. We included all clinical articles reporting more than 100 post‐operative PPFFx around total hip arthroplasty (THA). Outcomes included demographics, fracture type, risk factors and time to fracture. Results: A total of 12 868 PPFFx were reported across 18 eligible studies; 64% occurred following primary THA and 36% occurred after revision THA, and 66% of all fractures were in females. Vancouver B2 fractures were the most common type (39%). We found the odds of sustaining a PPFFx is significantly lower after a primary THA compared to revision THA (odds ratio 0.31, 95% confidence interval 0.24–0.40, P < 0.00001). The incidence of PPFFx is 2.96 per 1000 person‐years following primary THA compared to 9.08 per 1000 person‐years following revision THA (odds ratio 0.33, 95% confidence interval 0.27–0.40). The time to fracture was 6.03 years following primary THA and 4.08 years following revision THA. Gender and cementation did not significantly affect the odds of fracture. Conclusion: The odds of sustaining a PPFFx following revision THA is three times greater compared to primary THA. Other risk factors including gender and cementation did not affect the odds of fracture. Abstract : Periprosthetic fractures around total hip arthroplasty are increasing. Our systematic review and meta‐analysis demonstrates patients are three times more likely to sustain periprosthetic fractures after revision hip arthroplasty compared to primary hip arthroplasty, in both males and females.